2011
DOI: 10.1021/bm200618w
|View full text |Cite
|
Sign up to set email alerts
|

Development of Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) Fibers for Skin Tissue Engineering: Effects of Topography, Mechanical, and Chemical Stimuli

Abstract: Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), a biodegradable polyester, was electrospun to form defect-free fibers with high surface-area-to-volume ratio for skin regeneration. Several parameters such as solvent ratio, polymer concentration, applied voltage, flow rate, and tip-to-target distance were optimized to achieve defect-free morphology. The average diameter of the PHBV fibers was 724 ± 91 nm. PHBV was also solvent-cast to form 2-D films, and its mechanical properties, porosity, and degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(100 citation statements)
references
References 58 publications
4
92
0
4
Order By: Relevance
“…Thus, the gene expression of cells in a highly cross-linked or stiff scaffold will be different from those cultured on a more flexible scaffold of the same polymer and geometry. The elastin expression of MC3T3 cells cultured on poly(hydroxy butyrate-co-hydroxy valerate) scaffolds with different stiffness was found to be higher in the stiffer scaffold, probably to offset the stiffness of the scaffold [90]. The cells cultured on static and dynamic cultures have been found to differ in their functional expression [91].…”
Section: Mechanical Cuesmentioning
confidence: 96%
“…Thus, the gene expression of cells in a highly cross-linked or stiff scaffold will be different from those cultured on a more flexible scaffold of the same polymer and geometry. The elastin expression of MC3T3 cells cultured on poly(hydroxy butyrate-co-hydroxy valerate) scaffolds with different stiffness was found to be higher in the stiffer scaffold, probably to offset the stiffness of the scaffold [90]. The cells cultured on static and dynamic cultures have been found to differ in their functional expression [91].…”
Section: Mechanical Cuesmentioning
confidence: 96%
“…Kuppan et al [127] tried to develop growth factor loaded scaffolds. Studies have shown that growth factors help quicken the healing process.…”
Section: Skinmentioning
confidence: 99%
“…Вокруг всех типов имплантатов по периферии в окру-жающей фиброзно-мышечной ткани не отмече-но некрозов, кровоизлияний, гранулем и выра-женного отека. Реакция тканей на оперативное вмешательство и последующую имплантацию полимерных матриксов в общих чертах протека-ла по обычной схеме, характерной для раневого процесса и реакции на инородное тело, включая стадии травматического воспаления, образова-ния соединительной ткани, формирования и пе-рестройки рубца [6].…”
Section: материалы и методыunclassified
“…Данный класс полимеров характеризуется значительным разнообразием и включает в себя как моно-, так и сополимеры, которые, в свою очередь, обладают различными сроками биодеградации, физико-хи-мическими и физико-механическими свойствами [12]. Особый интерес представляет полигидрокси-бутират и полигидроксибутировалерат, нашедшие широкое применение в регенеративной медицине [6,7,8].…”
Section: Introductionunclassified